Change Trend and Attribution Analysis of Reference Evapotranspiration under Climate Change in the Northern China - Daxin Guo; Jørgen Eivind Olesen; Kiril Manevski; Johannes W. M. Pullens; Aoxiang Li; Enke Liu (Agronomy, 2023)
Reference evapotranspiration (ET0), an essential variable used to estimate crop evapotranspiration, is expected to change significantly under climate change. Detecting and attributing the change trend in ET0 to underlying drivers is therefore important to the adoption of agricultural water management under climate change. In this study, we focus on a typical agricultural region of the Fenwei Plain in northern China and use the Mann–Kendall test and contribution rate to detect the change and trend in ET0 at annual and seasonal scales and determine the major contribution factors to ET0 change for the baseline period (1985–2015) and the future period (2030–2060) based on high-resolution gridded data and climatic data from the Coupled Model Intercomparison Project Phase 6 (CMIP6). The results indicate that the annual ET0 of the Fenwei Plain showed a significant decreasing trend in the baseline period but insignificant and significant increasing trends in the future period under the SSP245 and SSP585 scenarios, respectively. The annual ET0 of the plain under the SSP245 and SSP585 scenarios increase by 4.6% and 3.0%, respectively, compared to the baseline period. The change and trend in ET0 between the four seasons are different in the baseline and future periods. Winter and autumn show clear increases in ET0. VPD is the major contribution factor to the ET0 change in the plain. The change in ET0 is mainly driven by the climatic variables that change the most rather than by the climatic variables that are the most sensitive to the ET0 change. The change and trend in ET0 in the plain showed clear spatial differences, especially between the eastern and western area of the plain. To adapt to the impact of climate change on ET0, the irrigation schedule of the crops cultivated in the plain, the cropping system and management of the irrigation district in the plain need to be adjusted according to the change characteristics of spatial and temporal ET0 in the future. These results contribute to understanding the impacts of climate change on evapotranspiration in the study region and provide spatial and temporal references for adaptation in managing agricultural water use and crop cultivation under climate change.